Determination of Dominant Mangrove Species and Comparison of Tree and Sapling Composition in The Mangrove Area of Sonsilo Village, West Likupang District, North Minahasa Regency - Mandei, Kania F.A.; Rumengan, Antonius P.; Paruntu, Carolus P.; Manembu, Indri S.; Ginting, Elvy L.; Djamaluddin, Rignolda (JURNAL PESISIR DAN LAUT TROPIS, 2026)
Mangrove forests are key ecosystems in tropical coastal areas that function as environmental stability guards through physical roles (preventing erosion and tsunamis), chemical (absorbing pollutants and storing carbon), and biological (marine biota habitat and source of biodiversity). This study aims to identify the species and determine the dominant species of mangroves and the comparison of tree and sapling composition in the mangrove area of ​​Sonsilo Village, West Likupang District, North Minahasa Regency.  The research was conducted over three months (September–November 2024) using a purposive sampling method to collect data on density, canopy cover, and species frequency. The results revealed seven mangrove species: A. marina, B. gymnorrhiza, C. tagal, R. apiculata, R. mucronata, S. alba, and X. granatum.  Among these, three species (B. gymnorrhiza, R. apiculata, and R. mucronata) were dominant at both tree and sapling levels, exhibiting the highest Importance Value Index (IVI).  Mangrove species diversity in the area is categorized as low to moderate, as indicated by the Shannon-Wiener Diversity Index (H'), reflecting that species richness is not yet fully optimal. Analysis of the Dominance Index (D) and Evenness Index (J') suggests a relatively even distribution of individuals among species.  The study recommends regular monitoring and evaluation, as well as conservation efforts, to maintain the stability of the mangrove ecosystem and support its sustainable use. These findings highlight the importance of biodiversity management in preserving the ecological balance of mangrove habitats. Keywords: Sonsilo Village, mangroves, mangroves composition